2023
DOI: 10.3390/jcm12154932
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review and Meta-Analysis of the Variants of the Obturatory Artery

Abstract: Background: Knowledge of vascular anatomy and its possible variations is essential for performing embolization or revascularization procedures and complex surgery in the pelvis. The obturator artery (OA) is a branch of the anterior division of the internal iliac artery (IIA), and it has the highest frequency of variation among branches of the internal iliac artery. Possible anomalies of the origin of the obturator artery (OA) should be known when performing pelvic and groin surgery, where its control or ligati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…In 1918, Lipshutz stated that "Probably no artery in the human body of proportionate size has so voluminous a literature as the obturator artery" [ 3 ]. This statement remains valid even in current times, as various original studies, systematic reviews, and meta-analyses on the anatomy of the ObA have been published in the literature and are continuously being published, showcasing new insights into this subject [ 5 , 7 , 8 ]. The origin of the ObA is remarkably variable, with some studies reporting a rate of variant ObA as high as 26% [ 8 ].…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…In 1918, Lipshutz stated that "Probably no artery in the human body of proportionate size has so voluminous a literature as the obturator artery" [ 3 ]. This statement remains valid even in current times, as various original studies, systematic reviews, and meta-analyses on the anatomy of the ObA have been published in the literature and are continuously being published, showcasing new insights into this subject [ 5 , 7 , 8 ]. The origin of the ObA is remarkably variable, with some studies reporting a rate of variant ObA as high as 26% [ 8 ].…”
Section: Discussionmentioning
confidence: 93%
“…The rarest cases fall under type E, where the artery originates from the external iliac artery, and type F, where it arises from the femoral artery. On the basis of this classification, Brachini et al [ 7 ] conducted a systematic review and meta-analysis showcasing the prevalences of ObA variants based on the available data in the literature. The study demonstrated that the most frequent origin of the ObA is from the anterior trunk of the internal iliac artery (61.6%), as described in the major anatomical textbooks.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations